2013
DOI: 10.1007/s13304-013-0199-y
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of suture skills during medical graduation by instructor-directed training: a randomized controlled study comparing senior medical students and faculty surgeons

Abstract: Due to shortage of time and limited availability of faculty surgeons to teach basic surgical skills during medical graduation, the search for alternative ways of simulated training with feedback is needed. The purpose of this study was to compare the simulated teaching of suture skills to novice medical students by senior medical students and by experienced faculty surgeons. Forty-eight novice medical students were randomly assigned to three practice conditions on bench model (n = 16): self-directed suture tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 42 publications
1
29
0
11
Order By: Relevance
“…Better OSCE results were reported for students taught by full-time faculty versus part-time faculty [64]. Regarding suturing skills, peer teaching and faculty teaching lead to equal practical test results [6] and there was also no difference between being taught by a non-surgical skills coach versus being taught by a surgeon [23]. For injections skills, peer-teaching lead to similar student skills like faculty teaching [59].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Better OSCE results were reported for students taught by full-time faculty versus part-time faculty [64]. Regarding suturing skills, peer teaching and faculty teaching lead to equal practical test results [6] and there was also no difference between being taught by a non-surgical skills coach versus being taught by a surgeon [23]. For injections skills, peer-teaching lead to similar student skills like faculty teaching [59].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, real-time feedback with an apparatus measuring the force applied by the learner’s hand while tying a knot led to an appropriate decrease of the force needed for this sensitive task compared to a group without this specific feedback [35]. While one study showed that suture training with feedback lead to better suturing skills than self-directed suture training [6], other studies reported that self-guided suturing practice [3] or a self-directed schedule for suturing practice [47] were associated with better suturing skill acquisition and additional expert feedback lead to no further skill improvement [31]. Furthermore, voluntary participation in reflective writing and skills practice [54] and voluntary practice with positively deviant peers [62] led to better clinical skill performance of participating students.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The University of Cape Town Surgical Society described by Leusink and Hoffmnan (2012) is also a student-run society that promotes medical and surgical research in order to motivate undergraduate medical students to pursue a career in surgery. Simulated training in suturing skills for junior students by senior students and surgeons was described by Denadai et al (2013). In the United Kingdom, the early introduction of basic surgical skills (BSS) program in the undergraduate curriculum increased the confidence and motivation of future medical graduates interested in surgical specialties, thus creating a recruitment pipeline for the surgical specialties (Hamaoui et al, 2013(Hamaoui et al, , 2014.…”
Section: Student Surgical Interest Groups and Surgical Competitionsmentioning
confidence: 99%